Victory Has a Thousand Fathers Detailed Counterinsurgency Case Studies - Paul, Christopher (RAND Corporation, 2010)
A collection of the 30 most recent resolved insurgencies, covering the period 1978 to 2008, along with a bank of 76 factors that helped or hindered the COIN force in each case and in each phase of each case, supplements an analysis of historical and contemporary insurgencies, providing valuable lessons for U.S. engagement in and support for COIN operations.